COMPARISON OF KINETIC AND STATISTICAL MODELLING APPROACHES FOR CONTINUOUS ELECTROCOAGULATION FOR PEAT WATER TREATMENT DESIGN SIMULATION - NUR SYAHIDA BINTI ABDUL JALAL, - (Universiti Malaysia Sarawak, 2022)
In Sarawak, peat water is one of the potential raw water sources as a domestic water supply, particularly for the communities of the rural areas that do not have access to the municipal water supply. However, the peat water must be treated before it is used as a water supply due to the high acidity level and concentration of organic material. The previous study has proved that the electrocoagulation process is an effective treatment system to treat peat water due to its high-efficiency pollutant removal, environmentally friendly and low-cost technology. However, most of the electrocoagulation process studies are performed on a small scale or lab scale only. Hence, scaling up the electrocoagulation system must be considered to fully utilise the electrocoagulation treatment and meet the growing water demand, especially for rural communities. This research study aims to propose a continuous electrocoagulation peat water treatment design model for domestic usage in Sarawak rural areas where the design simulation development will adopt the most suitable and high accuracy model which is either kinetic or statistical models. Then, the respective model will be further used to simulate the electrocoagulation process for scaling up purposes. It is found that the variable order kinetic (VOK) model derived from the Freundlich isotherm results reveals good agreement between the simulated data and the experimental data compared to VOKLangmuir and VOK-Jovanovic for kinetic modelling. This result indicates that the VOK-Freundlich model can predict the pollutant concentration at different treatment times by knowing the initial pollutant's concentration only. Besides, the predicted data obtained from the statistical model developed using Free Trial Design Expert 13 software by adopting Response Surface Methodology-Central Composite Design (RSM-CCD) is close to experimental data based on the coefficient of determination, R 2 and nonlinear chi-squared test, χ 2 . Hence, the statistical model is the most suitable approach to simulate the continuous electrocoagulation system in treating peat water. In conclusion, the developed statistical model can be applied to other continuous electrocoagulation for peat water treatment design systems where the electrocoagulation process can be predicted with various operating parameters, which are treatment time and current supply, without conducting an actual experiment.